Penerapan Steganografi File Gambar Menggunakan Metode Least Significant Bit (LSB) dan Algoritma Kriptografi Advanced Encryption Standard (AES) Berbasis Android - Endar Nirmala (Jurnal Informatika Universitas Pamulang, 2020)
Sending messages in the form of image files among the public or business people using the SMS feature from time to time is increasingly easy and often done. Messages can be sent from business partners or from clients. If the file is used for business purposes, it is an important secret for the company, and very dangerous if it falls into the hands of an undue. Therefore the security and confidentiality of the files sent are important and are very necessary in the exchange of information in this case in the form of image files through internet media. The method used to overcome this problem applies a combination of Advanced Encrytion Standard (AES) Cryptographic Algorithm techniques integrated with the Least Significant Bit (LSB) method. The integration of these techniques aims to provide protection or security systems on secret file messages in the form of images sent. The results of this study are applications called "StegoKripto" which is a combination of steganography and cryptography. The application runs on the Android platform which can encrypt text messages and hide the messages in pictures in the format .jpg and .png.